2008
DOI: 10.1017/s0033291708003656
|View full text |Cite
|
Sign up to set email alerts
|

Neurological soft signs and brain morphology in first-episode schizophrenia

Abstract: The pattern of cerebral changes associated with NSS clearly supports the model of 'cognitive dysmetria' with a disrupted cortico-cerebellar-thalamic-cortical circuit in schizophrenia. The variety of sites may correspond with the clinical diversity of NSS, which comprises both motor and sensory signs, and with the putative heterogeneity of the pathogenetic changes involved. That the respective associations did not apply for the healthy control group indicates that NSS in patients and controls refer to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
86
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 38 publications
(72 reference statements)
19
86
0
Order By: Relevance
“…Implicated motor systems include the cerebellum [13,54,55] and corticospinal tract [70,72], where we have previously described defects in Sema6A mutants [30,39]. The abnormalities in gait that we report here may reflect disrupted cellular organisation in the cerebellum [73].…”
Section: Comparison With the Pathology Of Psychiatric Disorderssupporting
confidence: 50%
See 1 more Smart Citation
“…Implicated motor systems include the cerebellum [13,54,55] and corticospinal tract [70,72], where we have previously described defects in Sema6A mutants [30,39]. The abnormalities in gait that we report here may reflect disrupted cellular organisation in the cerebellum [73].…”
Section: Comparison With the Pathology Of Psychiatric Disorderssupporting
confidence: 50%
“…Neuropathological studies of post mortem brains of SZ patients provide evidence for variable and subtle cytoarchitectural disturbances in cell positioning, packing, density and size in various parts of the brain, most notably the prefrontal cortex, hippocampal formation [4], thalamus [53] and cerebellum [54,55]. [56,57].…”
Section: Comparison With the Pathology Of Psychiatric Disordersmentioning
confidence: 99%
“…It is important to note that the detection of localized changes is not exclusive to FIRST but is also possible using voxel-based morphometry, a technique that was most commonly used in previous MRI studies on NSS in schizophrenia [12,16,29]. Inference in the latter technique relies on locally averaged gray matter segmentations and is therefore sensitive to the inaccuracy of tissue-type classification and arbitrary smoothing extents.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous structural magnetic resonance imaging (MRI) studies, increased NSS scores were found to be related to atrophic processes within the caudate nucleus [7,11,12,13], putamen [7,14], globus pallidus [7,13], thalamus [7,11,12,13,15], cerebellum [12,16], inferior and middle frontal gyri [12], and corpus callosum [17]. Studies using functional MRI techniques reported abnormal activation in the pre- and postcentral gyrus, the premotor area, and the middle and inferior frontal gyri in patients with higher NSS scores [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…58,59 NSS are also indicative of basal ganglia dysfunction, because a reduction of grey matter volume in different basal ganglia structures has been reported in a number of studies. [60][61][62] Furthermore, a recent study of functional and structural MRI in schizophrenia patients 63 showed that those with high levels of negative symptoms had diminished striatal activity during a working memory task. Despite converging evidence of basal ganglia dysfunction in deficit schizophrenia, and given the marked influence of antipsychotic medication on basal ganglia structures, 64 neuroimaging research on drug-naive patients with deficit schizophrenia is clearly warranted to confirm this hypothesis.…”
Section: Deficit Features and Primary Neurological Abnormalitiesmentioning
confidence: 99%